2016
DOI: 10.1074/jbc.m116.728956
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Interferes with Maturation of Amyloid-β Fibrillar Structure in the N Terminus

Abstract: Neurodegeneration is characterized by the ubiquitous presence of modifications in protein deposits. Despite their potential significance in the initiation and progression of neurodegenerative diseases, the effects of posttranslational modifications on the molecular properties of protein aggregates are largely unknown. Here, we study the Alzheimer disease-related amyloid-␤ (A␤) peptide and investigate how phosphorylation at serine 8 affects the structure of A␤ aggregates. Serine 8 is shown to be located in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
(48 reference statements)
5
27
0
Order By: Relevance
“…Our findings reveal that the pAb42 peptide aggregated in a similar manner to its native Ab42 peptide in an aqueous environment, but in the presence of phospholipid POPS/POPC LUVs or POPS/POPC/Chol LUVs, the pAb42 peptide aggregated more rapidly and to a much higher extent compared to the native peptide. These results are in agreement with the pAb40(S8) peptide, which also displayed a similar higher rate and amount of ThT reactive aggregate material compared to the native Ab40 peptide 5,22 while aggregation of pAb40(S26) 23 remained largely unchanged with only a slight increase in ThT absorbance after 30 h of incubation in a lipid-free model experiment. This increased aggregation of pAb42 was confirmed by the CD spectroscopy data, which revealed increased b-sheet formation in the presence of POPS/POPC/Chol LUVs (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings reveal that the pAb42 peptide aggregated in a similar manner to its native Ab42 peptide in an aqueous environment, but in the presence of phospholipid POPS/POPC LUVs or POPS/POPC/Chol LUVs, the pAb42 peptide aggregated more rapidly and to a much higher extent compared to the native peptide. These results are in agreement with the pAb40(S8) peptide, which also displayed a similar higher rate and amount of ThT reactive aggregate material compared to the native Ab40 peptide 5,22 while aggregation of pAb40(S26) 23 remained largely unchanged with only a slight increase in ThT absorbance after 30 h of incubation in a lipid-free model experiment. This increased aggregation of pAb42 was confirmed by the CD spectroscopy data, which revealed increased b-sheet formation in the presence of POPS/POPC/Chol LUVs (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…5 We and others show that pAb is largely in a disordered state. 5,22,23 The combined in vitro data suggest that a lipid environment is an important parameter for the promotion and formation of amyloid structures for the Ab peptide. We have previously shown that Ab peptide binding to neuronal cultures is a key determinant for inducing cell toxicity, with the notable key exception of the D-handed peptide, which while binding to neurons in culture was not toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation Plays Crucial Roles in F p␤ Formation-Recently, Rezaei-Ghaleh et al (46,55) have shown that phosphorylation at Ser 8 could impel the undergoing changes in local conformational dynamics of A␤40, induce the variations of N-terminal exposure of A␤ aggregates, and increase the fibril stability by promoting the formation of strong hydrogen bonds directly. We propose that different conformations of F p␤ fibrils may also be induced directly by phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…The Ab glycines are located within the peptide regions, which are potentially important for the function and/or toxic aggregation of Ab. For example, G9 is preceded by S8, a site of phosphorylation potentially linked to the progression of AD (32,33), and G25 and G29 are close to S26 whose phosphorylation interferes with the Ab fibrillar aggregation (34). It has also been suggested that G37 and G38 are involved in the turn formation in the C-terminal region, where its stabilization in the C-terminally extended Ab42 variant probably plays a role in the higher propensity of Ab42 to toxic aggregation (35).…”
Section: Selective Detection Of Multiple Glycine-related Singlets In mentioning
confidence: 99%